The Macroeconomic Effects of a Productivity Shock in the Nontraded Goods Sector - Tervala, Juha (Ekonomika, 2007)
This paper analyses the macroeconomic effects of a productivity shock in the nontraded goods sector using a small open economy model. The paper develops a simple dynamic general equilibrium model offering intuitive explanations of how a productivity shock affects a small open economy. The model gives a surprisingly pessimistic view on the benefits of productivity shocks. For example, a productivity shock has, except for one special case, a negative effect on the output of nontraded goods in the short run. This result differs from the results of RBC models. The paper gives an interesting insight into the possible effects that the introduction of the EU (European Union) services directive or GATS (General Agreement on Trade in Services) agreement may have.